Governing Corporate Social Responsibility Decoupling : The Effect of the Governance Committee on Corporate Social Responsibility Decoupling - Gull, Ammar Ali; Hussain, Nazim; Khan, Sana Akbar; Khan, Zaheer; Saeed, Asif (Springer, 2022)
This paper presents an examination of the relationship between the presence and composition of a corporate social responsibility (CSR) committee on the corporate governance board and CSR decoupling. Using a sample of listed firms drawn from 41 countries, we found that the presence of a CSR committee on the corporate board is negatively associated with CSR decoupling. We also noted that the nature of the industry to which a firm belongs, a firm's level of CSR orientation, and corporate governance quality strengthen such association. Further analysis of the relationship between the structure of the CSR committee and CSR decoupling shows that larger CSR committee size and a greater independence and longer tenure of its members negatively affect CSR decoupling. Our results are robust to various alternative specifications and offer important research and managerial implications. The findings of this study contribute to the growing literature on corporate governance and CSR.
Keywords: agency theory; Committee size; Corporate governance; Corporate social responsibility; CSR Committee; CSR decoupling; Gender diversity; Independence